The Effect of GIL Assisted Phyphox in Physics Learning towards Creative Thinking - ismu wahyudi; Eko Suyanto; Kartini Herlina; firda dwi fatmala (Jurnal Pembelajaran Fisika, 2020)
This study aims to determine how the effect of the Phyphox application on GIL based physics learning on students' creative thinking abilities. The sample of this research is students of class X IPA 3 SMA Negeri 1 Sukoharjo through purposive sampling technique. This study uses the One Group Pretest-Posttest design. The treatment was carried out through GIL based practicum activities on a simple pendulum assisted by Phyphox application. Data on students' creative thinking abilities were obtained using tests in the form of description questions. Data analysis technique using Paired Sample T-test. Based on data analysis, the average score of creative thinking ability has increased by 44%. Learning on simple pendulum materials assisted by Phyphox applications in five groups has an average acceleration due to gravity of 9,87  with an accuracy rate of 98,6%. The result is that GIL based physics learning assisted with the Phyphox application affects students' creative thinking abilities and produces accurate investigative data.Keywords: Creative Thinking Abilities, GIL, Online, Phyphox applications, SmartphoneDOI: http://dx.doi.org/10.23960/jpf.v8.n2.202002